Digital platforms and ecosystems as a factor of clusterization and innovative development of regions - D. l. Napolskikh (Модернизация, инновация, развитие, 2025)
Purpose: is to determine the impact of Russian digital platforms and ecosystems on the processes of innovative development and clustering of the economy of Russian regions.   Methods: the research is based on the scientific concepts and models within the framework of the theories of cluster development and digital transformation of the economy, in particular, the model of development of territorial innovation clusters. The following methods of statistical research were used: summary and grouping of statistical information, sample observation, correlation analysis.   Results: the attributive features of economic ecosystems are highlighted, which include innovation clusters, digital platforms and ecosystems. The theoretical approaches to defining a digital ecosystem are discussed, and the author provides definitions for the following concepts: digital platform, digital ecosystem, digital service, innovation cluster, industrial cluster, and innovative business networks. The features that characterize digital ecosystems are identified, and 12 Russian ecosystems are identified based on these features. Development models are systematized, classification criteria and types of digital platforms are clarified. The current trends in the development of digital platforms and ecosystems are considered, and the level of development of Russian ecosystems is assessed. The analysis of the use of digital platforms and other modern information technologies in Russian regions is carried out, the influence of the use of digital platforms on the processes of innovative development and clustering of subjects of innovative activity at the regional level is considered.   Conclusions and Relevance: the development of innovative and hybrid (innovation-transactional) platforms within the Russian digital ecosystems, as well as their integration with innovation clusters, are considered as a factor in the digital transformation of the economy of Russian regions. The author's model of an innovative hypercluster, which is a type of innovation clusters developing on the basis of digital platforms, is proposed as a new organizational form of this integration. The features of the innovative hypercluster model are multi-industry specialization, the trans-regional nature of economic activity and the multicore structure of network interactions of participants.